ANALISIS TINGKAT MINAT PEMBELAJARAN MENDALAM MATA PELAJARAN PJOK SISWA SMP NEGERI 2 KARANGDOWO - Aditya Yulianta Saputra; Pungki indarto; Anugrah Nur Wartadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students’ interest in deep learning in Physical Education, Sports, and Health (PJOK) among junior high school students. A descriptive quantitative approach with a survey method was employed. Data were collected using a closed-ended questionnaire based on a Likert scale consisting of 30 items covering four indicators: cognitive, affective, psychomotor, and engagement. The sample included 83 students selected from a population of 482 students at SMP Negeri 2 Karangdowo using simple random sampling. Data were analyzed using descriptive percentage techniques. The results showed that students’ interest in deep learning on the cognitive indicator reached 76% (high category), the affective indicator 84% (very high category), the psychomotor indicator 68% (high category), and the engagement indicator 74% (high category). Overall, the level of students’ interest in deep learning reached 75.52%, which falls into the high category. These findings indicate that students demonstrate a positive tendency toward PJOK learning, particularly in affective aspects. However, improvements are still needed in psychomotor skills and active engagement during learning activities. Therefore, teachers are encouraged to implement innovative, varied, and student-centered teaching strategies to enhance engagement, learning outcomes, and meaningful learning experience